PARENTAL GUIDANCE TO REDUCE HIGH RISK INTERNET ADDICTION - Masruroh, Fitriatul; Izzah, Fina Ulfatun Nailil; Putri, Ellyana Ilsan Eka (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Technology can be something that benefits us and can be something that is detrimental to us. We can feel the impact too. Especially when we look at this era, many young people are anti-social because they are too preoccupied with their world on social media compared to the real world, many young people are addicted to gadgets, a lack of culture, many young people and minors dress style they have also experienced many changes starting from very minimal clothing, sadly they are proud of that. The increasing number of online dating sites and pornographic content that are of interest to young people and can be accessed freely, so it's no wonder that there are more and more cases of sexual violence and even murder, originating from social media. So this is the background of the researcher to study this matter. The data collection technique uses the literature research method where data collection comes from articles, journals and books as study material. This research aims to provide readers with an understanding of the impact we feel from the media and the importance of the role of parents in accompanying and directing their children through their teenage years so that they can minimize the negative impact of social media.